Cosmic society towards a sociology of the universe - Dickens, Peter, 1940-; Ormrod, James S., 1980-; T&F eBooks (London ; New York : Routledge, 2007)
Tackling humanity's relationship with the universe, this fascinating text links social theory to classical and contemporary science, and proposes a new 'cosmic' social theory. It engages with a range of topical issues, including cyberspace, terorism, tourism, surveillance and globalisation.
1. The cosmic order, the social order and the self -- 2. The outer spatial fix -- 3. Capital, outer space and star wars -- 4. Satellites and social power -- 5. Space tourism and human identity -- 6. Industry and empire in space.
Includes bibliographical references (pages [195]-211) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Social change; Outer space -- Social aspects; Electronic books